IMPLEMENTASI PEMBIAYAAN KEPEMILIKAN EMAS DENGAN AKAD MURABAHAH PADA PRODUK SOLUSI EMAS HIJRAH DI BANK MUAMALAT KCP MAGELANG - Baihaqi Yahya; Chaidir Iswanaji; Ayunda Putri Nilasari (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
Bank Muamalat is a sharia-based bank in Indonesia, which has various financing products. Oneof the financing products available at Bank Muamalat is the Solusi Emas Hijrah (SOLEH) financing. Bank Muamalat creates opportunities for people who want to invest or own gold, in addition to its easy requirements, the financing is also free from usury. The research method applied in this study is a qualitative approach, with data collection techniques that include interviews, observations, and documentation. This financing procedure goes through several stages, including submission, feasibility analysis, agreement, disbursement of funds, and installment payment mechanisms by customers. However, behind that, there are obstacles such as late payments, which can affect the smoothness of transactions, due to a lack of understanding. This study is expected to provide useful insights for Islamic banking institutions in optimizing the implementation of the Murabahah agreement on gold financing products